STUDY PROPAGATION OF GSDIV (GROUPER SLEEPY DISEASE IRIDOVIRUS) IN CULTURED GF (GRUNT FIN) CELL - Ketut Mahardika; Indah Mastuti (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2013)
Grouper Sleepy Disease Iridovirus (GSDIV, genus Megalocityvirus) remain unsolved in Indonesian aquaculture. A GSDIV propagating study had been conducted to elaborate the capability of GSDIV replication in GF cell line. GSDIV isolate derived from spleen of diseased grouper fish were infected to GF cells line. GSDIV-infected GF cells were characterized by enlargement cells as CPE (cytophatic effect) which floated in cultured-medium. CPE-GSDIV was positively confirmed by PCR test. GSDIV-viral concentrations were ranging between 102.80-105.80 TCID50/mL. The newly passage GF cells were more sensitive to GSDIV which was shown by the abundance of CPE. GSDIV derived from GF cells were caused 10%-100% mortality of humpback grouper, Cromileptes altivelis.